Byssinosis, An Occupational Lung Disease: Diagnosis And Management - Mustofa, Syazili; Izzati, Marwah Aulia; Soeprihatini, Retno Ariza; Komala, Ramadhana; Silaen, David; Sinaga, Fransisca T.Y. (Jurnal Ilmu Kedokteran dan Kesehatan, 2025)
Byssinosis is an occupational lung disorder mainly caused by exposure of cotton dust during manufacturing. Over the years, it is well known as “Brown lung disease” and “cotton worker’s lung”. Byssinosis is characterized by respiratory symptoms such as cough, shortness of breath, chest tightness, and airway obstruction. The pathogenesis is still unclear. Despite the exposure to cotton dust, endotoxin release that resides in gram-negative in cotton dust also plays an important role in mediating byssinosis. Specify that supporting examination is not yet available. Thus, it is encouraging to relate the history of cotton dust exposure and the symptoms. In byssinosis, medication is given based on the symptoms that occur.